Minat Berwirausaha Ditinjau Dari Prestasi Praktik Kerja Bisnis Dan Kreativitas Pada Mahasiswa Program Studi Pendidikan Ekonomi Akuntansi Fakultas Keguruan Dan Ilmu Pendidikan Universitas Muhammadiyah Surakarta Angkatan 2013/2014 - WIBOWO, CATUR WAHYU; , Drs. Nur Chusni, SE.,M.Ag (2016)
Catur Wahyu Wibowo INTEREST IN ENTREPRENEURSHIP BASED ON PERFORMANCE WORK BUSINESS PRACTICES AND CREATIVITY IN STUDENTS STUDY ON ECONOMIC EDUCATION PROGRAM FACULTY OF ACCOUNTING TEACHING AND EDUCATION UNIVERSITY OF MUHAMMADIYAH SURAKARTA FORCE 2013/2014 ESSAY Accounting Education Teaching Faculty Of Education And The University Of Muhammadiyah Surakarta July, 2016 Improving the quality of human resources is an absolute prerequisite for achieving development goals one vehicle to improve the quality of human resources is education. Facts say, interest in entrepreneurship can give birth to someone to have the creativity to create something determination expected. It also can create something new with independent manner. The purpose of this study was to investigate the influence achievement labor practices against the business interest in entrepreneurship, in order to investigate the influence of creativity on the interest in entrepreneurship, in order to investigate the influence of achievement working practices of business and creativity to the interest in entrepreneurship. This research method is quantitative descriptive with 119 students of the subject of accounting education in a manner proportional force 2013/2014 and insindental sampling. The data in this research is multiple linear regression analysis, t -test, F, and the relative contribution and effective. Based on the results of the regression analysis obtained regression equation: Y = 3.482 + 0.359 X1 + 0.584 X2. The equation shows that the interest in entrepreneurship is influenced by the achievements of the working practices of business and creativity. The conclusions drawn are: 1) There is an effect of the achievement of business working practices acceptable interest in entrepreneurship. This is based on multiple linear regression analysis (t test) note that tcount> t , 3.018> 2.000 and the significance value <0.05, namely 0.000 with the relative contribution of 33% and 21% effective contribution. 2) There is an effect of the interest in entrepreneurship creativity acceptable. This is based on multiple linear regression analysis (t test) note that tcount> t table table , namely 5.806> 2.000 and the significance value <0.05, namely 0.000 with the relative contribution of 67% and 43% effective contribution. 3) There is an effect of achievement working practices of business and creativity to the interest in entrepreneurship can be accepted. This is based on multiple linear regression analysis of variance (F test) is known that F count> F table, ie 165.283> 3.150 and the significance value <0.05, namely 0.000. 4) The coefficient of determination (R2) of 0.640 indicates that the influence of achievement working practices of business and creativity to the interest in entrepreneurship is by 64%, while the rest influenced by other variables. Keywords: Achievement of business working practices, creativity and interest in entrepreneurship.